Perkembangan Persuratkhabaran bahasa Mandarin di Malaysia dan Peranannya Dalam Masyarakat Cina : The Development of Mandarin Language Newspapers in Malaysia and Its Role in Chinese Society - Kuok Tiung, Lee; Hasim, Mohd Safar; Basrah Bee, Bazsley Bee (Jurnal Pengajian Media Malaysia, 2011)
The establishment of Chinese newspapers in Malaysia began with the migration of overseas Chinese (Huaqiao) to Malaysia. Several of the pioneer Chinese newspapers such as Kwong Wah Yit Poh (1910), Nanyang Siang Pau (1923), Sin Chew Jit Poh (1929), Overseas Chinese Daily News (1932), and China Press (1946) are still in existence today. This article explores the development of the Chinese newspapers by tracing their chronology; analyses the factors that contributed to the emergence of the newspapers, and identifies their challenges. A salient aspect of the contemporary mediascape pertaining to Chinese newspapers is the ownership of the newspapers. In the past, the ownership of newspapers revolved around individual companies, whereas, majority of the newspapers in Malaysia now are owned by two Chinese tycoons, both from Sarawak, through Media Chinese International Limited (MCIL) and Kumpulan KTS. This article will show how the Chinese newspapers played a crucial role in advocating and fighting for Chinese education, culture and identity. Penubuhan surat khabar Cina di Malaysia bermula dengan penghijrahan orang Cina ke luar negara (Huaqiao) ke Malaysia. Beberapa akhbar perintis Cina seperti Kwong Wah Yit Poh (1910), Nanyang Siang Pau (1923), Sin Chew Jit Poh (1929), Berita Harian Cina Luar Negara (1932), dan China Press (1946) masih ada . Artikel ini meneroka perkembangan akhbar Cina dengan menelusuri kronologi mereka; menganalisis faktor-faktor yang menyumbang kepada kemunculan surat khabar, dan mengenal pasti cabaran mereka. Aspek penting dari pemandangan media kontemporari yang berkaitan dengan surat khabar Cina adalah hak milik surat khabar. Pada masa lalu, pemilikan surat khabar berputar di sekitar syarikat individu, sedangkan, sebahagian besar surat khabar di Malaysia kini dimiliki oleh dua hartawan Cina, baik dari Sarawak, melalui Media Chinese International Limited (MCIL) dan Kumpulan KTS. Artikel ini akan menunjukkan bagaimana surat khabar China memainkan peranan penting dalam menyokong dan memperjuangkan pendidikan, budaya dan identiti orang Cina.